Infrared Spectroscopy for Online Measurement of Tars, Water, and Permanent Gases in Biomass Gasification. Issue 6 (June 2021) - Pushp, Mohit; Brackmann, Christian; Davidsson, Kent
Online measurements of the raw gas composition, including tars and water, during biomass gasification provide valuable information in fundamental investigations and for process control. Mainly consisting of hydrocarbons, tars can, in principle, be measured using Fourier transform infrared (FT-IR) spectroscopy. However, an instrument subjected to raw gas runs the risk of condensation of tars on optical components and subsequent malfunction. Therefore, an external cell, heated to at least  400 ℃, has been designed to ensure that tars remain in the gas phase during FT-IR measurements. The cell was used for on-line FT-IR measurements of permanent gases (CO, CO2, CH4 ), water, and tars during the operation of a lab-scale downdraft gasifier using wood pellets, bark pellets, and char chips. Based on calibration, the measurement error of permanent gases was estimated to be 0.2%. Concentrations evaluated from spectral signatures of hydrocarbons in tar are in good agreement with results from solid-phase adsorption measurements and correlated well with operational changes in the gasifier. Graphical Abstract